2013
DOI: 10.1017/s1431927613000317
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lead and Copper on the Cellular Architecture and Metabolism of the Red AlgaGracilaria domingensis

Abstract: The effect of lead and copper on apical segments of Gracilaria domingensis was examined. Over a period of 7 days, the segments were cultivated with concentrations of 5 and 10 ppm under laboratory conditions. The samples were processed for light, confocal, and electron microscopy, as well as histochemistry, to evaluate growth rates, mitochondrial activity, protein levels, chlorophyll a, phycobiliproteins, and carotenoids. After 7 days of exposure to lead and copper, growth rates were slower than control, and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 49 publications
(79 reference statements)
3
17
0
1
Order By: Relevance
“…Similar results were observed by Collén et al (2003) in Gracilaria tenuistipitata C. F. Chang & B. M. Xia treated with Cd and Cu and by Gouveia et al (2013) in Gracilaria domingensis (Kützing) Sonder ex Dickie treated with Cu. They proposed that the decreased content of protein could have been caused by toxic effects to protein or amino acid synthesis, as well as nitrate reduction.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results were observed by Collén et al (2003) in Gracilaria tenuistipitata C. F. Chang & B. M. Xia treated with Cd and Cu and by Gouveia et al (2013) in Gracilaria domingensis (Kützing) Sonder ex Dickie treated with Cu. They proposed that the decreased content of protein could have been caused by toxic effects to protein or amino acid synthesis, as well as nitrate reduction.…”
Section: Discussionsupporting
confidence: 80%
“…Phycobiliproteins, the characteristic reddish pigment of red macroalgae, are the most sensitive antenna pigment, localized externally to the reaction center and the first photosynthetic pigment to decrease in concentration under light stress (Bouzon et al 2012, Gouveia et al 2013. Under the most extreme condition of this experiment (day 7, 1000 μmol photons m −2 s −1 ), the apical portions of G. tenuifrons were completely yellowish (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…In some cases, like in Cu and Zn-treated Scenedesmus sp. cells, Car content was unchanged during the treatments showing that some algal species use other mechanisms in protection from metal-induced oxidative stress , while in some red algae, Pb and Cu treatments significantly decreased total carotenoid content (Gouveia et al 2013).…”
Section: Carotenoids and Phycobilinsmentioning
confidence: 88%
“…Studies on Anabaena flos-aquae show that cellular proteins, including phycocyanin, represent the main targets of metal toxicity, which was more pronounced in the protein profile after Cu treatment under different temperature levels, compared to Cd treatment in the same temperature range (Surosz and Palinska 2005). Pb and Cu exposure significantly decreased the total phycobiliprotein content in rhodophyte Gracilaria domingensis (Gouveia et al 2013), which was also observed for several cyanobacterial species, such as in S. platensis when exposed to Pb (Arunakumara and Zhang 2007) and after Ni or Pb exposure in Oscillatoria sp. and Westiellopsis sp., particularly in longer treatments.…”
Section: Carotenoids and Phycobilinsmentioning
confidence: 98%